BALLROOM DANCE AS A WAY TO IMPROVE THE QUALITY OF LIFE OF A GROUP OF ELDERLY IN THE CITY OF URUCUIA-MG - Barbosa, Edmar Alves; Alves Miranda Andrade, Juliana (RENEF, 2022)
This study aimed to verify how the practice of ballroom dancing helps as a means of benefits to health in the third age population in the city of Urucuia-Mg, as well as to identify and point out the benefits of ballroom dancing as a physical activity practice in elderly population, in order to evaluate the benefits of ballroom dancing practiced by elderly people in the city of Urucuia-MG. For this purpose was used as a method of data collection the local field research, in which it is intended to prove through reports the relevance of dance in the physical and emotional well-being of the elderly. From the data analysis, it can be seen that the importance of dance is not only as a leisure and entertainment option, but also as an alternative for improving the quality of life and preventing diseases.Finally, through the study carried out and the questionnaire applied, it was possible to confirm that ballroom dancing as a physical activity provided fun and health for the participants, promoting the interaction of all in a single context, seeking great experiences and socialization. Keywords: Physical activity. Ballroom dance. Qualityoflife. Third Age.